Who Benefits from AI? Project-Level Evidence on Labor Demand, Operations and Profitability - Erdem Dogukan Yilmaz; Christian Peukert (CESifo GmbH, 2024)
We examine how the adoption of digital automation technology affects labor demand, operations and profitability in the context of the logistics industry. Our data covers 9,300 digital automation projects in a multinational company involving service robots and machine learning-based software from 2019 to 2021, alongside fine-grained labor and operations data. To identify causal effects, we leverage exogenous variation from supply-chain disruptions and travel restrictions during COVID-19 and an import ban on information and communication technologies imposed by the Trump administration. We find that total labor cost increased after the adoption of digital automation technology, attributable to increased labor demand and more reliance on temporary workers. However, managerial hours declined, possibly due to increased efficiency. Furthermore, digital automation technology increased revenue and profit through a reduction in operational cost, improved utilization of warehouse space, and higher profit margins. However, the effects of digital automation technology are not homogeneous. We highlight substantial complementarities between hardware and software technologies. Management units that only use software technology experience only half the increase in revenue and profit.
Keywords: 330; digital automation technology; robots; artificial intelligence; future of work